EH-EH: Ernest Hemingway and Euskal Herria / the Basque Country. 20th Biennial International Hemingway Conference - Frederick H. White (Литература двух Америк)
Every other year, the Hemingway Society organizes a conference dedicated to its namesake Ernest Hemingway. The conference location migrates between international and domestic US cities where the writer has some connection. On 14–20 July 2024, the conference was held in two cities in Spain — Bilbao and San Sebastian. Each city has relevance for both the biographical and literary Hemingway. San Sebastian is featured prominently in The Sun Also Rises. Bilbao and the surrounding area is relevant geographically for the novel For Whom the Bell Tolls. Spain, in general, is depicted in numerous short stories and Hemingway’s play, The Fifth Column. Therefore, the scene was set for compelling papers, presentations and discussions. Like many single-author conferences, this one has a diverse group of participants including academics, fans, would-be Hemingways, authors and simply the curious. From the academic offerings, much attention was given to the three panels of the Hemingway Letters Project. The Out of the Archives series of panels included one that was concentrated on Ernest and Mary Hemingway’s experiences with the Soviet Union. The closing session was offered by Valerie Hemingway, who worked as a secretary for the American author and is now one of the last people able to give a first-hand account of Hemingway’s life and literary works.